Assessment of genetic damage induced by dental bleaching agents on mouse lymphoma cells by single cell gel (comet) assay - Ribeiro, D. A.; Marques, MEA; Salvadori, Daisy Maria Favero [UNESP] (Blackwell Publishing, 2005)
Dental bleaching is a simple and conservative procedure for aesthetic restoration of vital discoloured teeth. However, dental bleaching agents may represent a hazard to human health, especially by causing DNA strand breaks. Genotoxicity tests form an important part of cancer research and risk assessment of potential carcinogens. In the current study, the genotoxic potential associated with exposure to dental bleaching agents was assessed by the single cell gel (comet) assay in vitro. Six commercial dental bleaching agents (Clarigel Gold - Dentsply; Whitespeed - Discus Dental; Nite White - Discus Dental; Magic Bleaching - Vigodent; Whiteness HP - FGM and Lase Peroxide - DMC) were exposed to mouse lymphoma cells in vitro. The results pointed out that all dental bleaching agents tested contributed to the DNA damage as depicted by the mean tail moment. Clear concentration-related effects were obtained for DNA damaging, being the strongest effect observed at the highest dose of the hydrogen peroxide (Whiteness HP and Lase Peroxide, at 35% concentration). on the contrary, Whitespeed (Discus Dental) induced the lowest level of DNA breakage. Taken together, these results suggest that dental bleaching agents may be a factor that increases the level of DNA damage as detected by the single cell gel (comet) assay.
Keywords: dental bleaching; mouse lymphoma cells; genotoxicity; comet assay